AKIBAT HUKUM TERHADAP PEMBELI YANG MENGIKAT PERJANJIAN PENGIKATAN JUAL BELI DENGAN PENGEMBANG RUMAH SUSUN YANG DINYATAKAN PAILIT (CONTOH KASUS: PUTUSAN MAHKAMAH AGUNG NO. 261 K/PDT.SUS-PAILIT/2016) - Andreani Dewanto; Suyud Margono (Fakultas Hukum Universitas Tarumanagara, 2020)
Unfinished sale and purchase of the apartement unit before the apartement developer was declared bankrupt by the decision of the bankrupt statement causing the Purchase Binding Agreement (PPJB) agreed by the apartement unit buyer and the apartement developer could not proceed to the Sale and Purchase Act (AJB). This has resulted in the bankruptcy law regarding the ownership status of apartement unit to buyers who have paid in full. Thus creating problems, what about the legal consequences on buyers who bind PPJB with apartment developers who are declared bankrupt? This study uses a normative research method with a statutory approach. Based on the discussion that has been analyzed, it can be concluded that the transfer of ownership rights to apartement unit occurred at the time of the sale and purchase between the apartement developer and the apartement unit buyer as outlined in the AJB made before the authorized PPAT so that the apartement unit buying and selling object based on PPJB had not been transferred to the buyer . With the stated bankruptcy of the apartement developer, apartement unit which is used as the object of buying and selling in PPJB enters the bankrupt assets, so that the apartement unit still belongs to the apartement developer which is then put into bankrupt assets. The PPJB between the apartement developer and the buyer of apartement unit shall be deleted by the entry into force of Article 37 Paragraph (1) of Law Number 37 of 2002 concerning Bankruptcy and Suspension of Debt Payment Obligations. Therefore, if the buyer is disadvantaged because of the elimination of the PPJB, then the buyer can propose himself as a concurrent creditor to get compensation.